A Screen of Autophagy Compounds Implicates the Proteasome in Mammalian Aminoglycoside-Induced Hair Cell Damage - Draf, Clara; Wyrick, Taylor; Chavez, Eduardo; Pak, Kwang; Kurabi, Arwa; Leichtle, Anke; Dazert, Stefan; Ryan, Allen F. (Frontiers in Cell and Developmental Biology, 2021)
Introduction Autophagy is a degradative pathway to safely break down and recycle dysfunctional cellular components. There is prior evidence of autophagy participation during hair cell (HC) damage. Our goal was to screen compounds targeting different aspects of autophagy for their effects on HC loss due to an ototoxic aminoglycoside, gentamicin (GM). Methods The SELLECKChem autophagy compound library, consisting of 154 compounds with defined autophagy inducing or inhibitory activity, was used for targeted screening in vitro model of ototoxicity. Organ of Corti from postnatal days 3-5 pou4f3/GFP transgenic mice (HCs express green fluorescent protein) were utilized. The organs were micro-dissected, and basal and middle turns divided into micro-explants individually placed into the single wells of a 96-well plate. Samples were treated with 200μM of GM plus three dosages of tested compound and cultured for 72 hours. Negative controls were treated with media only; positive ototoxicity controls were treated with GM only. Results The majority of the library compounds had no effect on GM-induced HC loss. However, 18 compounds exhibited a significant, protective effect, two compounds were protective at low dosage but showed enhanced GM toxicity at higher doses and one compound was toxic to HCs in the absence of GM. Conclusions This study evaluated many autophagy compounds that have not been tested previously on HCs. The disparate results obtained underscore the complexity of autophagy events that can influence HC responses to aminoglycosides, but also implicate the proteosome as an important damage mechanism. The screening results can serve as basis for further studies with protective compounds as potential drug targets.